2006
DOI: 10.1007/s00412-006-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the sister chromatid cohesion apparatus in gene expression, development, and human syndromes

Abstract: The sister chromatid cohesion apparatus mediates physical pairing of duplicated chromosomes. This pairing is essential for appropriate distribution of chromosomes into the daughter cells upon cell division. Recent evidence shows that the cohesion apparatus, which is a significant structural component of chromosomes during interphase, also affects gene expression and development. The Cornelia de Lange (CdLS) and Roberts/SC phocomelia (RBS/SC) genetic syndromes in humans are caused by mutations affecting compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
149
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(154 citation statements)
references
References 107 publications
(157 reference statements)
5
149
0
Order By: Relevance
“…They also showed that cohesin binds to cut in multiple cell types and that a unique pds5 mutation that reduces binding of cohesin to chromosomes increases cut expression (Dorsett et al 2005). Combined, these findings and the genetic linkage between Nipped-B's roles in gene expression and sister chromatid cohesion reported here support the hypothesis that Nipped-B facilitates cut expression by alleviating negative effects of cohesin (Dorsett 2004(Dorsett , 2007. This model suggests that cohesin binding to cut inhibits expression and by maintaining a dynamic cohesin chromosome-binding equilibrium, Nipped-B facilitates cohesin removal or relocation.…”
Section: Nipped-b Heat Repeat Mutations Link Nipped-b's Roles In Genesupporting
confidence: 75%
See 1 more Smart Citation
“…They also showed that cohesin binds to cut in multiple cell types and that a unique pds5 mutation that reduces binding of cohesin to chromosomes increases cut expression (Dorsett et al 2005). Combined, these findings and the genetic linkage between Nipped-B's roles in gene expression and sister chromatid cohesion reported here support the hypothesis that Nipped-B facilitates cut expression by alleviating negative effects of cohesin (Dorsett 2004(Dorsett , 2007. This model suggests that cohesin binding to cut inhibits expression and by maintaining a dynamic cohesin chromosome-binding equilibrium, Nipped-B facilitates cohesin removal or relocation.…”
Section: Nipped-b Heat Repeat Mutations Link Nipped-b's Roles In Genesupporting
confidence: 75%
“…Like the Nipped-B family, cohesin also has roles besides sister chromatid cohesion in meiosis, DNA repair, gene expression, and human development (reviewed in Dorsett 2007;Nasmyth and Haering 2005;Hagstrom and Meyer 2003;Hirano 2006;Revenkova and Jessberger 2006). Thus, a central question is whether regulation of cohesin also explains the functions of the Nipped-B family proteins in gene expression and meiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the requirement of cohesin for sister chromatid cohesion after DNA replication during S-phase is well documented, its function in transcription regulation is unknown (25). Previous studies in yeast, Drosophila, and zebrafish suggest that cohesin influences transcription.…”
Section: Discussionmentioning
confidence: 99%
“…CdLS patients display slow growth, mental retardation, and defects in limbs and organs (Dorsett 2007;Jackson et al 1993;Strachan 2005). Most do not show cohesion defects (Kaur et al 2005;Vrouwe et al 2007), suggesting that the diverse developmental deficits are caused by gene expression changes similar to those in Drosophila.…”
Section: Introductionmentioning
confidence: 99%